On the Issue of Expert Terms in Forensic Linguistics - V. О. Kuznetsov (Теория и практика судебной экспертизы)
The article addresses the problem of using a deliberative category of “expert terms” in forensic linguistics. The issue is related to the questions of the relations between the linguistic and legal terms standing for so-called speech offenses and the use of legal concepts when wording expert tasks and conclusions. Basing on the understanding of the concept “expert terms” of the general theory of forensic science and the provisions of the theory of expert terms of forensic psychology under which the expert terms hold the position between legal and basic sciences’ concepts, an attempt is made to contemplate theoretically the category of “expert terms” as applied to the forensic linguistics. The article also shows the algorithm for developing forensic linguistic terms depending on the wording of a legal provision on examples from expert practice.